ANALISIS PANJANG TUNGKAI DAN DAYA LEDAK OTOT TUNGKAI TERHADAP KECEPATAN LARI SPRINT 60 METER (CENDEKIA: JURNAL ILMIAH PENDIDIKAN, 2022)
The results of observations in while technique starting the explosive power or repulsion that produced are still lacking, so there is a lack of encouragement to start running and when running, the range of legs is not long so students need many steps to reach the finish line. The purpose of this study was 1) to determine the performance of leg length on the speed of the 60 meter sprint. 2) to find out if there is explosive power performance of leg muscles on the 60 meter sprint running speed. 3) to determine the performance of leg length and leg muscle explosive power on the 60 meter sprint running speed. The technique of collecting samples was random and analyzed descriptively and inferentially through the SPSS 25 program at a significant level of 0.05. The results showed that: 1) there was a significant performance between leg length and 60 meter sprint running speed. 2) significant performance between the explosive power of the leg muscles and the speed of the 60 meter sprint. 3) significant performance between leg length and leg muscle explosive power to the 60 meter sprint running speed.  Key words: Leg length, leg muscle explosive power, sprint running speed.